Outpatient Hysteroscopic Emptying of a Submucosal Uterine Cystic Lesion - Attilio, Di Spiezio Sardo (Society of Laparoendoscopic Surgeons, 2007)
BACKGROUND: Uterine cystic neoformations are rare, but they should always be investigated to differentiate a benign from a malignant pathology. Transvaginal ultra-sonography, MRI, and blood tests are the main investigations for diagnosing these lesions, avoiding over- or undertreatment. Hysteroscopy might represent a helpful tool both for its diagnostic and therapeutic properties. METHODS: We report the hysteroscopic emptying of a cystic-degenerated leiomyoma with a 5-Fr flexible needle inserted through the operative channel of a 5-mm continuous-flow operative office hysteroscope in an outpatient setting. RESULTS: The cystic lesion was successfully emptied. The hystopathological result of the target biopsies performed on the cystic wall was cystic degeneration of a leiomyoma. CONCLUSION: This needle is normally used in gynecology to instill intrauterine local anesthesia under a hysteroscopic view. We adapted it to drain a fluid-filled lesion, identifying a further application of this instrument.